Effectiveness of social norms perception in virtual simulation for teaching ethical decision-making in international business - Gaonan Song (Environment and Social Psychology, 2025)
With the deepening of globalization, ethical decision-making issues in international business activities have become increasingly complex, creating an urgent need to cultivate business professionals with cross-cultural ethical competencies. This study aims to validate the effectiveness of pedagogical intervention in social norm perception on international business ethical decision-making within virtual simulation contexts. Adopting a 2×2×3 mixed experimental design, 312 undergraduate and graduate students from business schools in South China were recruited as participants, randomly assigned to either a virtual simulation teaching group or a traditional case-based teaching group, and stratified by cultural background (Eastern vs. Western). Through an 8-week teaching intervention, participants’ international business ethical decision-making abilities and social norm perception levels were measured at three time points: baseline, post-test, and delayed test. The results revealed that: (1) Virtual simulation teaching intervention significantly enhanced students’ ethical decision-making abilities, with the experimental group showing an improvement of 1.46 points and an effect size of 2.04, significantly outperforming the control group’s improvement of 0.60 points; (2) Social norm perception played a significant mediating role between teaching intervention and ethical decision-making ability, with a mediation effect of 1.04, accounting for 71.2% of the total effect, where descriptive norm perception demonstrated the strongest mediating effect; (3) Virtual simulation teaching showed the most significant effects in the dimensions of moral sensitivity identification and ethical conflict analysis, with effect sizes reaching 2.58 and 2.30, respectively; (4) Cultural background significantly moderated the teaching effectiveness, with students from Eastern cultural backgrounds benefiting significantly more (d=2.75) than those from Western cultural backgrounds (d=1.57); (5) The teaching effects demonstrated good sustainability, with delayed testing showing that the virtual simulation group maintained high performance levels. This study confirms the effectiveness of virtual simulation technology in business ethics education, providing theoretical foundations and practical guidance for constructing personalized teaching models based on social norm perception, and holds significant importance for promoting the digital transformation and quality enhancement of international business ethics education.